"It's uncomfortable for us to be called sisters": an exploratory study into the experiences of male nurses in a Johannesburg hospital, South Africa - Kalemba, Joshua (My University, 2016)
The aim of this study is to understand the experiences of male nurses as they work in women-dominated workplace. The focus of other studies has been on: the ‘glass escalator’ and the hidden advantages for men in the so called ‘female’ professions; masculinity at work; the experiences of men in female dominated occupations and the experiences of men in caring professions. In South Africa, many studies on masculinity have been carried out that focus on the gender issues of southern Africa such as, causes and prevention of intimate partner violence; young men and the construction of masculinity, implications for HIV/AIDS, conflict, and violence; contemporary masculinities particularly the gendered cultural politics and hegemonic masculinities/masculinity in South African: culture, power and gender politics. But there is a dearth of literature on the issue of men in gender concentrated occupations, like nursing, in South Africa. This study seeks to fill the gap in understanding of how South African men experience their masculine gender identity in the context of engaging in work which is supposedly feminine by employing a qualitative, semi-structured interview approach of 15 male nurses of a hospital in Johannesburg, South Africa. This study argues that male nurses tend to portray hegemonic masculinity as their gender identity is simultaneously being configured, misconfigured and reconfigured in the workplace.
A Research Report submitted in partial fulfilment of a Master of Arts in Industrial Sociology by coursework and Research Report. Faculty of Humanities, University of the Witwatersrand. 15 March 2016
Keywords: Male nurses--South Africa.; Masculinity--South Africa.; Sex discrimination against men--South Africa